2015
DOI: 10.5194/nhess-15-1551-2015
|View full text |Cite
|
Sign up to set email alerts
|

PM<sub>1</sub> geochemical and mineralogical characterization using SEM-EDX to identify particle origin – Agri Valley pilot area (Basilicata, southern Italy)

Abstract: Abstract.A PM 1 geochemical and mineralogical study using Scanning Electron Microscopy (SEM) was performed on a pilot site in the Agri Valley which is close to the oil pre-treatment plant (C.O.V.A) of Europe's largest on-shore hydrocarbon reservoir. The study identified PM 1 geochemical and mineralogical characters in the period before, during and immediately after a burning torch flare event. The finer fraction (D Fe < 0.7 µm) consisted mainly of secondary particles and soot. In the coarser fraction (D Fe ≥ 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 70 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…Furthermore the high TEM resolution is often not required for aerosol particles larger than a few tens of nanometres. Scanning electron microscopes provides a lower resolutions, but recent advances have made it possible to automatically scan large areas of a sample, process the acquired images, locate particles, and perform subsequent EDS analysis without user intervention except for the initial setup 24,25 . As a result, automated SEM/EDS analysis makes it possible to obtain sufficient data on the single particle level to allow for a meaningful statistical analysis of an aerosol population, including both physical and elemental composition data 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the high TEM resolution is often not required for aerosol particles larger than a few tens of nanometres. Scanning electron microscopes provides a lower resolutions, but recent advances have made it possible to automatically scan large areas of a sample, process the acquired images, locate particles, and perform subsequent EDS analysis without user intervention except for the initial setup 24,25 . As a result, automated SEM/EDS analysis makes it possible to obtain sufficient data on the single particle level to allow for a meaningful statistical analysis of an aerosol population, including both physical and elemental composition data 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In India, most of the research studies on atmospheric PM have focused on the elemental composition of particles [3][4][5]. However, several researchers have investigated both the physical (shape and size) and elemental characteristics of atmospheric PM through scanning electron microscope (SEM) and SEM-energy-dispersive X-ray spectroscopy (SEM-EDX), respectively [6][7][8]. At the coastal city of Chennai, located in the south of India, SEM analysis revealed particle types such as soot, minerals and salts, whose origination can be traced to combustion, crustal and marine sources, respectively [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…During this period, a gas-flaring episode due to a malfunction of the COVA plant occurred. The study of the PM 1 geochemical and mineralogical features before, during and immediately after this episode highlighted the influence of the COVA emissions on the PM 1 collected in terms of soot and S-rich particle as well as the significant role played by a Saharan dust event occurred during the gas flaring episode in supplying geogenic aerosol components to the PM 1 (Margiotta et al 2015). The influence of the COVA plant emissions on the air quality of the area under study was also confirmed by the results obtained by statistically analyzing the atmospheric concentrations of 17 trace elements (Al, Ca, Cd, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, P, Pb, S, Ti and Zn) measured at 59 biomonitoring stations installed by the CNR-IMAA and covering an area of about 100 km 2 around the COVA plant (Caggiano et al 2015).…”
Section: Air Qualitymentioning
confidence: 99%